Political Event Risk (Elections and Election Announcements) on LQ45 Stock Returns - Nurfitri Desliniati; Retno Andika (Keizai, 2025)
This study is motivated by the need to understand the impact of political event risk on Indonesia’s capital market, especially on highly liquid and large-cap stocks such as those in the LQ45 index. Political events, both domestic and international, can influence investor behavior and create stock price volatility. Therefore, this research aims to analyze the effect of political event risk on LQ45 stock returns. The study applies a quantitative approach with an event study method. The sample includes companies listed in the LQ45 index during the observation period, which covers several key political events. Secondary data in the form of daily stock prices were analyzed by calculating returns around the event window to identify any significant impact of political events on stock returns. The event window used in this study spans 30 days before (H-30) and 30 days after (H+30) the political events. The results show different impacts of political event risk across the two phases. During the election result announcement, political event risk had a significant positive effect on LQ45 stock returns, reflecting greater certainty about Indonesia’s political direction and increased investor confidence. Conversely, during the election period, political event risk had no significant effect on LQ45 stock returns, indicating that the market had already anticipated these dynamics. These findings highlight the importance of distinguishing political event phases when assessing market responses.